2023
DOI: 10.3390/computers12020028
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Local Area Network Performance Improvement Using Ad Hoc Routing Protocols in a Wireless Network

Abstract: Wireless Communication has become one of the most popular types of communication networks because of the many services it provides; however, it has experienced several challenges in improving network performance. VLAN (Virtual Local Area Network) is a different approach which enables a network administrator to create a logical network from a physical network. By dividing a large network into smaller networks, VLAN technology improves network efficiency, management, and security. This study includes VLAN for wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Then, in order to lower the SNR to a predetermined threshold, a signal is sent using that frequency range. Jamming assaults may raise the danger of Denial-of-Service (DoS) attacks, increase communication latency, and decrease energy efficiency DoS [22,23]. Fig.…”
Section: Jamming Attacksmentioning
confidence: 99%
“…Then, in order to lower the SNR to a predetermined threshold, a signal is sent using that frequency range. Jamming assaults may raise the danger of Denial-of-Service (DoS) attacks, increase communication latency, and decrease energy efficiency DoS [22,23]. Fig.…”
Section: Jamming Attacksmentioning
confidence: 99%
“…Shayma W. N. et al, assesses the Ad-Hoc Routing protocols' effect in Virtual Area Network using Riverbed Modeler modeled scenarios. The outcomes showed that the performance of WSN had been improved using these ad hoc protocols in terms of delay and throughput [9]. Shayma W. N. et al, determined the throughput and delay QoS parameters to improve the MANET's performance deficiency caused by the interference of jamming attacks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These criteria include the network topology, bandwidth availability, power consumption of the devices, and network congestion [6]. Different forms of IoT applications require different kinds of routing protocols since each kind of protocol has its own unique set of features [7].…”
Section: *Author For Correspondencementioning
confidence: 99%